2018
DOI: 10.12973/iji.2018.11420a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Material Use on Mathematics Achievement: A Meta-Analysis

Abstract: As a result of rapid development in technology, utilizing materials in education has become important. To date, researchers have often explored the effects of using educational materials in mathematics instruction on academic achievement. The purpose of this study was to combine the empirical evidence regarding the effectiveness of educational materials in mathematics. For this aim, a meta-analysis method was used in the current research. In line with the aim of the research, 54 experimental studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Also, while using materials students had the opportunity to be able to work at their own pace, which might be the reason for the positive effect of materials on the learning of students. On the other hand, the results of some studies revealed an insignificant difference in terms of student achievement (Enki, 2014;Kul, Çelik, & Aksu, 2018;Öztürk, 2012;Tataroğlu, 2009). The reason for this result might be the duration of material uasage.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, while using materials students had the opportunity to be able to work at their own pace, which might be the reason for the positive effect of materials on the learning of students. On the other hand, the results of some studies revealed an insignificant difference in terms of student achievement (Enki, 2014;Kul, Çelik, & Aksu, 2018;Öztürk, 2012;Tataroğlu, 2009). The reason for this result might be the duration of material uasage.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…In addition, Enki (2014) found that the experimental and control group did not differ significantly when unit cubes, symmetry mirrors, and acetate papers were included in the teaching-learning process. Kul et al (2018) in their metareview study did not find a significant difference in terms of the effectiveness of instruction between teaching by including materials and without including them, but they found meaningful differences in terms of mathematics topic, type of material, and application time. For this reason, there is a need for systematic investigation of studies about the effects of material usage while teaching different subjects of mathematics in different grade levels on the cognitive and affective outcomes of students.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In mathematics education, learning settings that employ different teaching materials like symbols, concrete objects, pictures and diagrams are gaining importance in the concretization of concepts and relationships (Clements & McMillen, 1996;Lesh, Post, & Behr, 1987). It was often reported that using concrete material is an effective way to increase the mathematics achievement (Sherman & Bisanz, 2009;Kul, Celik, & Aksu, 2018). It was stated that the use of concrete materials in education makes it easier for students to learn mathematical concepts (Boggan, Harper, & Whitmire, 2010;Carbonneau, Marley, & Selig, 2013), makes conceptual learning possible (Dienes, 1973), ensures opportunities for permanent learning (Cass, Cates, Smith, & Jackson, 2003;Martin & Schwartz, 2005), increases individual critical thinking skills (Apperson, Laws, & Scepansky, 2006), provides opportunities for problem solving (Kelly, 2006), and contributes to the development of positive attitudes towards learning (Aydogdu-Iskenderoglu & Taskin, 2015;Kelly, 2006;Yetkin-Ozdemir, 2008;Aydin-Unal & Ipek, 2009).…”
Section: Introductionmentioning
confidence: 99%